FREQUENCY ANALYSIS OF BIMODAL CEPHEIDS - Bezdenezhnyi, V. P. (Одеські астрономічні публікації, 2017)
The Fourier analyses of photoelectric Berdnikov’s (1992) V-observations some of bimodal Cepheids (AS Cas, EW Sct, V367 Sct, TU Gas and CO Aur) are performed. For stars with two known periods new identifications are carried out. EV Aql and δ Sge are attributed to bimodal Cepheids and added to them. More detailed subdivision of bimodal Cepheids is suggested on the ground of their mode classification.